2005
DOI: 10.1002/app.22287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bound polymer on cure characteristics of natural rubber compounds reinforced with different types of carbon blacks

Abstract: Rubber compounds are reinforced with fillers such as carbon black and silica. The cure characteristics of a filled rubber compound vary with the filler type and content. The influence of the type of carbon black on the cure characteristics of carbon black filled natural rubber compounds is investigated using two types of carbon black (N220 and N550), which are different in primary size and structure. The cure time and cure rate become faster as the carbon black content increases. The crosslink density also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…For CB grade A and C, tightly bound rubber volume fraction increases with CB content. This effect is more pronounced for CB C. Results have already been observed in literature7, 9, 27 and could be governed by different phenomena: (a) formation of tightly bound rubber adsorbed around filler, (b) formation of occluded rubber inside aggregates, and (c) formation of trapped rubber between aggregates. Results give also a tightly bound rubber volume fraction evolution more pronounced for CB C when CB content increases.…”
Section: Resultsmentioning
confidence: 99%
“…For CB grade A and C, tightly bound rubber volume fraction increases with CB content. This effect is more pronounced for CB C. Results have already been observed in literature7, 9, 27 and could be governed by different phenomena: (a) formation of tightly bound rubber adsorbed around filler, (b) formation of occluded rubber inside aggregates, and (c) formation of trapped rubber between aggregates. Results give also a tightly bound rubber volume fraction evolution more pronounced for CB C when CB content increases.…”
Section: Resultsmentioning
confidence: 99%
“…10 The increased concentration of curatives in the rubber matrix due to the presence of the tightly bound rubber could also be used to explain the cure acceleration. 34 It is found that, at any given filler content, the scorch time and optimum cure time are in the following order; N330 > CNT > XE2-B. The torque difference (MH-ML) is found to increase with increasing filler content.…”
Section: Compound Propertiesmentioning
confidence: 94%
“…In this method, the vulcanization reaction considered to be proportional to the change of the rubber stiffness. Cotten [10], Gerspacher et al [11], Mahalling et al [12], Choi [13], Choi et al [14], and Wang et al [15] have investigated the rubber vulcanization using rheometer. In order to obtain the rubber compound as raw material of rubber goods, the process of mastication and milling is required.…”
Section: Introductionmentioning
confidence: 99%